Will great power competition in the South Atlantic spill Into Antarctica? - Bruno Arpi; Anthony Press (2021)
International politics is facing a return of great power competition. President Joe Biden has stated that the United States will not allow China to become the leading, wealthiest, and most powerful country in the world. In this context, this “new great game” seems to have found the Southwest Atlantic, and this has direct implications for Antarctica. However, it is important to question whether wider global political tensions will necessarily be replicated in Antarctica. While the Southwest Atlantic has been prone to geopolitical tensions and territorial disputes have existed in the region for the last three centuries, the area south of 60º South latitude, governed under the Antarctic Treaty System (ATS), enjoys a special political and legal status that has successfully kept this region free of armed conflict and significant political tension for the last six decades.